Small is beautiful: Experimental evidence of donors' preferences for charities - Sarah Borgloh; Astrid Dannenberg; Bodo Aretz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
This paper studies the effect of information about a charity's size on individuals' donations to that charity. We conducted a framed field experiment with a non-student sample, in which subjects had the opportunity to donate for various charitable purposes. The results show that if subjects are to choose between large organizations with high annual revenues and small organizations with low revenues, they prefer the small organizations. We also provide insights why donors prefer the small organizations and discriminate between different theoretical approaches.
Keywords: H41; C91; D83; 330; charitable contributions; information; framed field experiment; fundraising; Spende; Nonprofit-Organisation; Test; Spendensammlung